RANCANG BANGUN PELUNCUR ELEKTROMAGNETIK DENGAN SUPLAI KAPASITOR - Adi Guna Subawa, I Nyoman; Prapto Sudarmojo, Yanu; Arta Wijaya, I Wayan (Jurnal SPEKTRUM, 2020)
Electromagnetic launchers are devices that use electromagnetic forces to launch high-speed projectiles, utilizing accelerated armature shifts along with a pair of conductive rails. Electromagnetic launchers have been studied as high-speed ballistic launchers for various applications such as military weapons to space launches. Based on the development of capacitor technology and the limited development of electromagnetic launchers, especially in the field of launching high-speed projectiles with capacitor supply as the development of electromagnetic weapons technology, research was carried out by making the design of electromagnetic launchers with capacitor supply to produce high-speed projectiles (more than 180m/s based on variations in rifle bullet speed) as the development of electromagnetic weapons technology. The results of the research on the design of electromagnetic launchers with capacitor supply obtained the final projectile velocity value of 200,644 m/s, which consists of three main components namely the rail system, the gas injector, and the supply system.